Preparation and Characterization of high‐strength poly(ether ether ketone) films. Issue 9 (3rd December 2013) - Li, Wenlei; Wang, Guibin; Jiang, Zhenhua; Liu, Chuan; Huo, Pengfei; Zhang, Shuling
ABSTRACT High‐strength poly(ether ether ketone) (PEEK) films were prepared through melt extrusion followed by stretching. The tensile strength, orientation, and crystallization behaviors of PEEK films were characterized by universal testing machine, thermomechanical analysis, wide‐angle X‐ray diffraction, and differential scanning calorimetry. The results indicated that the tensile strength of PEEK films mainly depended on the stretching rate (ν), stretching temperature (T), and stretching ratio (λL). Moreover, the tensile strength of the stretched PEEK film (333 MPa) was almost four times higher than that of the unstretched PEEK film (87 MPa) under an optimized condition. This is attributed to a synergistic effect of orientation and crystallization in the stretching process, and the influence of orientation is stronger than that of the crystallization on the improvement of the tensile strength of PEEK films. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40172.